2018
DOI: 10.1007/s11604-018-0753-0
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-GSA SPECT/CT fusion imaging for hepatectomy candidates with extremely deteriorated ICG value

Abstract: Tc-GSA SPECT/CT fusion imaging enables more accurate liver function assessment than the ICG test in patients with severely deteriorated ICG values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…26 Because 99m Tc-GSA SPECT scintigraphy is affected neither by portal-systemic shunting nor jaundice, this imaging examination enables more accurate liver functional assessment in such conditions compared to the ICGR15 test. 27 Further study including 99m Tc-GSA SPECT scintigraphy would be required.…”
Section: Discussionmentioning
confidence: 99%
“…26 Because 99m Tc-GSA SPECT scintigraphy is affected neither by portal-systemic shunting nor jaundice, this imaging examination enables more accurate liver functional assessment in such conditions compared to the ICGR15 test. 27 Further study including 99m Tc-GSA SPECT scintigraphy would be required.…”
Section: Discussionmentioning
confidence: 99%
“…This test allows for an indirect assessment of function and metabolic activity of hepatocytes. A low rate of galactose elimination may indicate a liver failure or other pathology [72,73].…”
Section: Clinical Methods For Assessing Functional and Structural Chamentioning
confidence: 99%
“…as established by Sumiyoshi et al [73], can be distorted by abnormal hepatic blood flow; this factor limits the method application in patients with intrahepatic shunts. The test is also not applicable for patients with excretory defects or jaundice.…”
Section: Reviewsmentioning
confidence: 99%
“…The majority of the studies investigated both major and minor surgery. Four studies also included non-operative interventions such as radiofrequency ablation, transarterial embolization or chemoembolization, percutaneous ethanol injection, or microwave coagulation therapy [31,52,75,87]. The vast majority of trials reported on postoperative LF or mortality.…”
Section: Study Demographicsmentioning
confidence: 99%